Parental Satisfaction with the Quality of Care in an Early Intervention Service for Children with Visual Impairment: A Retrospective Longitudinal Study - Tiziana Battistin; Elena Mercuriali; Carlotta Borghini; Maria Eleonora Reffo; Agnese Suppiej (MDPI AG, 2024)
The fundamental role of vision during development and the nurturing role of early intersubjectivity have enabled the Robert Hollman Foundation to develop an early intervention program providing holistic support to visually impaired children and their families, where fostering parent-infant interactions is at the heart of our care. The aim of this study is to understand how parents perceive this approach. It is an eleven-year retrospective study of children following the Robert Hollman Foundation's early intervention program, in which parents' (n = 1086) perceptions of quality of care were measured through the administration of a specifically designed 4-point scale questionnaire. Annual longitudinal trends of parents' perceptions were calculated for every single response. Parents reported a very high satisfaction value in 21/23 questions (Mean > 3.7 out of a maximum score of 4, with the highest scores in human and soft skills of professionals) with a statistically positive trend (p < 0.05), throughout the period considered. Our core approach, based on an individualized nurturing relational support, has been appreciated and confirmed by the high satisfaction reported in the questionnaires by parents of children with visual impairment. We therefore hypothesize that parent-infant relationship-based and individualized approaches may help parents achieve better health, well-being, and quality of daily life for their children.